Does tranexamic acid have a positive effect on the outcome of older multiple trauma patients on antithrombotic drugs? An analysis using the TraumaRegister DGU® - Fitschen-Oestern, Stefanie; Franke, Georg Maximilian; Kirsten, Nora; Lefering, Rolf; Lippross, Sebastian; Schröder, Ove; Klüter, Tim; Müller, Michael; Seekamp, Andreas; , TraumaRegister DGU (Frontiers in Medicine, 2024)
Background Acute hemorrhage is one of the most common causes of death in multiple trauma patients. Due to physiological changes, pre-existing conditions, and medication, older trauma patients are more prone to poor prognosis. Tranexamic acid (TXA) has been shown to be beneficial in multiple trauma patients with acute hemorrhage in general. The relation of tranexamic acid administration on survival in elderly trauma patients with pre-existing anticoagulation is the objective of this study. Therefore, we used the database of the TraumaRegister DGU® (TR-DGU), which documents data on severely injured trauma patients. Methods In this retrospective analysis, we evaluated the TR-DGU data from 16,713 primary admitted patients with multiple trauma and age > =50 years from 2015 to 2019. Patients with pre-existing anticoagulation and TXA administration (996 patients, 6%), pre-existing anticoagulation without TXA administration (4,807 patients, 28.8%), without anticoagulation as premedication but TXA administration (1,957 patients, 11.7%), and without anticoagulation and TXA administration (8,953 patients, 53.6%) were identified. A regression analysis was performed to investigate the influence of pre-existing antithrombotic drugs and TXA on mortality. A propensity score was created in patients with pre-existing anticoagulation, and matching was performed for better comparability of patients with and without TXA administration. Results Retrospective trauma patients who underwent tranexamic acid administration were older and had a higher ISS than patients without tranexamic acid donation. Predicted mortality (according to the RISC II Score) and observed mortality were higher in the group with tranexamic acid administration. The regression analysis showed that TXA administration was associated with lower mortality rates within the first 24 h in older patients with anticoagulation as premedication. The propensity score analysis referred to higher fluid requirement, higher requirement of blood transfusion, and longer hospital stay in the group with tranexamic acid administration. There was no increase in complications. Despite higher transfusion volumes, the tranexamic acid group had a comparable all-cause mortality rate. Conclusion TXA administration in older trauma patients is associated with a reduced 24-h mortality rate after trauma, without increased risk of thromboembolic events. There is no relationship between tranexamic acid and overall mortality in patients with anticoagulation as premedication. Considering pre-existing anticoagulation, tranexamic acid may be recommended in elderly trauma patients with acute bleeding.